Experimental Studies of Energy-Efficient Beams in Buildings and Structures of the Oil and Gas Complex - Chichulina, Kseniia; Chichulin, Viktor; ., . (International Journal of Engineering and Technology, 2018)
This study presents the results of experimental tests of new structural solutions for beams with double profiled trapezoidal wall and uneven pitch of corrugations. Tests of such structures have been performed for the first time. This determined the goals and objectives of the experiment. The probabilistic characteristics (mathematical expectation, mean square deviation) of the strength of the profiled wall material and the limit parameters of the bearing capacity of beams elements with profiled walls have been determined. This further allows us to calculate the failure probability of structures belonging to this type in the form of a system of elements. Experimental tests in the nodes of beams with profiled walls gave the opportunity to assess the nature of the work in such structures, to build the dependence of deformation from loads in dangerous cross sections of the samples and graphs of the deflections to determine the characteristic space structures and the patterns of transition to the ultimate state. Experimental studies have shown the effectiveness of the profiled wall inclusion in the beam bending and confirmed the feasibility of its use for buildings and structures of the oil and gas complex. It was experimentally revealed that the plane stress state of the profiled wall is characterized by small values of normal stresses at the level of the middle axis with a tendency of increasing in the direction of connection with the shelves. The novelty of the research is in the experimental analysis of features of the new beam assemblies with a double profiled wall and confirmed the possibility of using corrugated thin-walled profiles in the beam walls. The prospect and advantages as for the application of the developed designs in industrial facilities of the oil and gas complex have been proved. Peculiarities of carrying out experiments of thin-walled designs are revealed.Â Â